8d+8=7d+9

Simple and best practice solution for 8d+8=7d+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8d+8=7d+9 equation:


Simplifying
8d + 8 = 7d + 9

Reorder the terms:
8 + 8d = 7d + 9

Reorder the terms:
8 + 8d = 9 + 7d

Solving
8 + 8d = 9 + 7d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-7d' to each side of the equation.
8 + 8d + -7d = 9 + 7d + -7d

Combine like terms: 8d + -7d = 1d
8 + 1d = 9 + 7d + -7d

Combine like terms: 7d + -7d = 0
8 + 1d = 9 + 0
8 + 1d = 9

Add '-8' to each side of the equation.
8 + -8 + 1d = 9 + -8

Combine like terms: 8 + -8 = 0
0 + 1d = 9 + -8
1d = 9 + -8

Combine like terms: 9 + -8 = 1
1d = 1

Divide each side by '1'.
d = 1

Simplifying
d = 1

See similar equations:

| x+12=yforx | | 5x+7=-2+8x | | c/3=70 | | d^2-10d+26=8 | | 13x+14=-12 | | 9x^2+144x+576=0 | | 9x+28-7x=-3.3 | | 5n-3(n-8)=4+3n | | 4=w/12 | | y-5+5= | | 11-4a=-7(a-1)+1 | | -(2x+3)=-5+7x | | 3x-3-x-4x=5x+12-12x | | b^2-4b+1=-5 | | 9(y-1)=4y+4 | | -6(r+6)=-37-5r | | -6b-6b=8-4b-7b | | p+7=8 | | (-x)-2x=(-7) | | 2=2-7n-2n | | 3x+4-2x-x=4x-4 | | -2(5x+5)+2x-1=-43 | | -2+3x=-6+7(6x-5) | | 5/k=2/7 | | 20-22+3= | | 2n+40=2n+10 | | 10=x*(x+3x) | | 8/3=5/b | | 4(8n-3)=-12+7n | | n/7=4/3 | | X^2(2x+3y-6)= | | 0=-16t^2+16t+672 |

Equations solver categories